Cross-Talk Between Adipose Tissue Health, Myocardial Metabolism and Vascular Function: The Adipose-Myocardial and Adipose-Vascular Axes - Iozzo, Patricia; Angela Guzzardi, Maria (Current Pharmaceutical Design, 2016)
Alterations in myocardial metabolism and blood flow have been described in patients with metabolic disorders, cardiovascular disease and cardiomyopathies, and have been implicated in the pathogenesis or prognosis of cardiac conditions. Adipose tissue dysfunction occurs in the above categories of patients. Adipose tissue plays a fundamental role in the modulation and selection of nutrients reaching the myocardium, and adipocytes secrete adipokines and other molecules affecting myocardial metabolism and regulating vascular function. In turn, the myocardium secretes a series of peptides affecting adipose tissue metabolism, and adipose tissue vascularization and perfusion contribute to the maintenance of adipose tissue health. This review addresses the reciprocal interaction linking adipose tissue to myocardial metabolism and vascular function. We summarize evidence of factors released by adipose tissue that affect cardiac metabolism and vice versa. Then, we address the role of adipose tissue in regulating vascular health, and examine whether adipose tissue hypoperfusion is causative or defensive of adipose tissue dysfunction.
Keywords: obesity